Crystal structure and anti-inflammatory activity of (E)-7-fluoro-2-((5-methoxypyridin-3-yl)methylene)-3,4-dihydronaphthalen-1(2H)-one, C17H14FNO2 - Sun Jia-Jia; Zhang Xiao-Fan; Meng Qing-Guo; Li Hong-Juan; Wang Chun-Hua (Zeitschrift für Kristallographie - New Crystal Structures)
C17H14FNO2, monoclinic, C2/c (no. 15), a = 15.5754(12) Å, b = 7.4828(6) Å, c = 23.0981(18) Å, β = 90.797(7)°, V = 2691.8(4) Å3, Z = 8, Rgt(F) = 0.0442, wRref(F2) = 0.1096, T = 100(1)° K.